Analyzing Nurses Midwives' Experience and its Influence on Knowledge and Performance in Postpartum Hemorrhage Management - Atiya Mohammed; Tebin Jihan (Kufa Journal for Nursing Sciences)
Background: Postpartum haemorrhage (PPH) stands as the foremost contributor to maternal mortality rates worldwide. It represents the most prevalent form of obstetric haemorrhage, with even healthy mothers facing potential fatality within a mere two-hour window if PPH remains undetected. This study explores the correlation between the professional experience, Knowledge, and Performance of nurses/midwives concerning postpartum haemorrhage.